Anti-inertial loading platform: New method of resisting inertia in transport. (October 2022) - Lan, Tianxiang; Yang, Guotian; Ding, Xiying
Highlights: Proposed a new mathematical model of resisting the inertia in transport. A root locus analysis is adopted for stability analysis of mathematical model. Adaptive parameter method is used to improve the motion performance of the device under heavy load. Implemented prototype mechanical device and tested on a pickup truck. Abstract: To mitigate the disadvantages of cargo protection in the transportation industry, a vehicle-mounted loading platform that can offset the inertial force is proposed herein, and its prototype is built. This device solves the problem of inertia in cargo transportation using a novel concept. The device uses an accelerometer for signal acquisition and a brushless gear motor as the driving force. Based on the current acceleration value of the vehicle, the tilting angle of the loading platform is changed such that the resultant force of the loaded object is perpendicular to the loading platform. Prior to building the real prototype, a root locus analysis of the entire model is performed using the Simulink/Analysis tool. Subsequently, the method is optimized to solve problems in stability analysis. Finally, the prototype is evaluated in a pickup truck, and both the measured acceleration-angle curve and the actual performance of the prototype in the truck confirm excellent application value of the vehicle-mounted anti-inertial loading platform.